PENGARUH TATA KELOLA PERUSAHAAN, PROFITABILITAS, DAN PENGHINDARAN PAJAK TERHADAP NILAI PERUSAHAAN - Aida Farah Dinah; Darsono Darsono (Diponegoro Journal of Accounting, 2017)
This study aims to examine the effect of corporate governance, profitability, and tax avoidance of the firm’s value. The measurement of the corporate governance is based on the Corporate Governance Index score. The questions are divided to five groups according to the OECD principles; rights of shareholders, equal treatment of shareholders, role of stakeholders, disclosure and transparency, and board responsibilities. Profitability is proxied by Return on Asset. The measurement of independent variable tax avoidance is based on proxy Effective Tax Rate. Dependent variable in this research is the firm’s value measured by Price to Book Value.Total sample in this study are 210 companies listed in Indonesia Stock Exchange during 2013-2015. The sampling method used is purposive sampling method with predetermined criteria. This study uses multiple linear regression analysis to examine the effect of the corporate governance, profitability, and tax avoidance on firm’s value.The result of this study shows that there is positive and significant affect of corporate governance and profitability to firm value. Furthermore, the tax avoidance has negative and significant effect on firm value measured by Price to Book Value.